A study on structural changes of placenta in pregnancy induced hypertensive pregnancies in eastern India - Biswanath Baskey; Ratnadeep Poddar; Iman Sinha; Joydip Saha; Akash Kusum Banerjee (Al Ameen Medical College, 2024)
Background: Complications of pregnancy are reflected in placenta. Placenta is the mirror of maternal and foetal status. So a study of placenta and new born will help to identify the disease by which mother is affected in pregnancies of pregnancy induced hypertension. Aim: Our study aimed in study of morphology, morphometry and histology of placenta in normal pregnancy and in pregnancy induced hypertensive (PIH) mothers. This study also correlates the birth weight and height of the new born babies of both the mothers of normal pregnancy and PIH. Materials and Methods: 50 booked cases (25-normal pregnancy and 25 PIH) have been studied in an institution in eastern India. Antenatal check up of these cases were made routinely. After delivery, placentas were examined for morphological, morphometric, histological and histopathological parameters and features. Birth height and weight of the newborn babies were documented in each case. Finally, parameters were analyzed in between both the groups. Results: Placental weight and volume reduced significantly in P.I.H. mothers and the reduction of placental area was suggestive of pregnancy induced hypertension. Incidence of gross calcification in placenta, retro placental blood clots and infarction increased markedly in pregnancy induced hypertensive mothers. There has been increased incidence of syncitial knots and syncytio-trophoblast in PIH. Thickening of basement membrane, increased intervillous space and fibrinoid necrosis were associated with PIH. Conclusion: Structural changes in the placenta, macroscopic ad well as microscopic, during pregnancy induced hypertension has been detrimental to the foetus, which is the main focus of our study.